Awá Legends as a Pedagogical Resource to Improve Reading Skills in Junior Students at Colegio de Bachillerato Universitario UTN - Guaña Vaca, Rosario Maribel (2024)
Use Awá legends to improve the reading skill in senior students at Colegio de Bachillerato Universitario UTN, 2022 – 2023 academic year.